Voice-Based Home Security and SMS Gateway Using Arduino Uno Microcontroller And Passive Infra Red Sensor - Yuda Irawan; Yulisman Yulisman; Naima Belarbi; Mbunwe Muncho Josephine (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
The development of advanced Information Technology by greatly improving human thought patterns. This home security problem can be overcome with a security system that can be delivered to homeowners via SMS notification (Short Message Service) compilation of plow sensors accepting people who enter the compilation house when it is installed and the system is in standby and the alarm will sound and the sound module has been designed to provide information about the movement in the house. To minimize this crime, the need for tools that can help improve home security. Based on the overall system test results in accordance with the desired that the security system can be used in a supported system, where when the PIR sensor supports movement the buzzer will sound, the red LED lights up, the sound module issues the expected voice message and the GSM module will send a message to the homeowner's mobile number. PIR sensor will work optimally if the object is detected by humans with a maximum distance of 6 meters. While for animals (cats), the success is only 40%, and plants cannot be detected at all by the PIR sensor and the GSM module will send a verification message to the cellphone owner in less than 1 minute. This tool is more effectively used in a room that provides valuable items, for example in a room or other room